2017
DOI: 10.1002/acr.22974
|View full text |Cite
|
Sign up to set email alerts
|

Severe Health‐Related Quality of Life Impairment in Active Primary Sjögren's Syndrome and Patient‐Reported Outcomes: Data From a Large Therapeutic Trial

Abstract: The cardinal symptoms of primary SS (dryness, pain, and fatigue, best assessed using the ESSPRI) are stronger predictors of HRQOL impairment than systemic involvement (assessed by the ESSDAI) and should be used as end points in future therapeutic trials focusing on patients' well-being. New consensual and data-driven response criteria are needed for primary SS studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
1
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 30 publications
4
57
1
3
Order By: Relevance
“…However, the TEARS and TRACTISS trials did not observe a significant effect of rituximab treatment on SF-36 scores, compared with placebo. This is consistent with findings that subjective symptoms improved only slightly (TEARS) or not at all (TRACTISS) in the rituximab group, as subjective symptoms are strong predictors of health-related qualityof-life in pSS patients [53].…”
Section: Effects On Quality Of Lifesupporting
confidence: 91%
“…However, the TEARS and TRACTISS trials did not observe a significant effect of rituximab treatment on SF-36 scores, compared with placebo. This is consistent with findings that subjective symptoms improved only slightly (TEARS) or not at all (TRACTISS) in the rituximab group, as subjective symptoms are strong predictors of health-related qualityof-life in pSS patients [53].…”
Section: Effects On Quality Of Lifesupporting
confidence: 91%
“…Cardinal symptoms include mouth and eye dryness, marked fatigue and wide-spread pain, which have a profound effect on the quality of life of patients with pSS 2 . These symptoms are non-specific and can occur with many other conditions 3, 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Cornec et al. () correlated quality of life measures as determined by the Short Form 36 (SF‐36) with ratings of SS disease activity. They found that patient ESSPRI ratings, measuring subjective symptoms, were strongly correlated with SF‐36, with significant correlations between ESSPRI rating and each individual domain of the SF‐36.…”
Section: Resultsmentioning
confidence: 99%